Uncertain research country rankings. Should we continue producing uncertain rankings? - Rodríguez-Navarro Alonso (Journal of Data and Information Science, 2025)
Citation-based assessments of countries’ research capabilities often misrepresent their ability to achieve breakthrough advancements. These assessments commonly classify Japan as a developing country, which contradicts its prominent scientific standing. The purpose of this study is to investigate the underlying causes of such inaccurate assessments and to propose methods for conducting more reliable evaluations.